Bains publics Se laver en ville (1850-2000) - Richelle, Sophie (MSH series, 2023)
With Bains publics, Sophie Richelle offers an original double story. That of the history of communal baths, understood as the places where it was possible to have a wash outside home at a lower cost in the nineteenth and twentieth centuries. And that of the historian's quest being conducted.